PENERAPAN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN ARAH MINAT SISWA PADA SMA N 14 PADANG BERBASIS WEB DENGAN METODE AHP - Arman Arman; Wahyudi Wahyudi; Desi Erlina (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2019)
The problem that has occurred so far is that many students have difficulty in determining the direction of interest in the 14th high school in Padang. Since the 2013 curriculum was treated, this rule has been applied to the interests, talents, abilities and expectations with specialization chosen to be aligned and directly proportional, so that students' abilities can be improved. But the results are still not optimal. The principle is to run optimally and the problems that have occurred so far can be overcome. Then a system is needed to facilitate the BK teacher in determining the direction of interest of the student's majors by using the AHP method. So that the problems faced by the teacher can be overcome. In the AHP method all values are given the weight of each criterion such as report cards, UN scores and interest test scores for majors that are suitable for these students and the work of the BK teacher can also be helped. The results of the study from student data Givania Pembega name with a report card value of 0.1554, the average score of UN 0.0449 and the value of interest 0.0729 can be a total value of 0.2732 with interest majors classified in the Science Department With the existence of a decision support system for determining direction This student interest can be used as a tool in making decisions for students in determining the direction of their interests, and can also help BK teachers in determining the direction of their students' interests. In conducting this research, the research method uses the SDLC method and tools for system design using UML and programming languages using PHP and MySQL.Keywords: SPK, Specialization, Students, AHP, UML, Mysql